Indonesian High School Learners’ Fear of Negative Evaluation and Ought-to L2 Self - Kezia Marcellova Glory; Adaninggar Septi Subekti (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The study aimed to investigate the Indonesian high school science learners’ Fear of Negative Evaluation (FNE), which is a second language (L2) anxiety construct, Ought to L2 Self (OL2S), an L2 motivation construct, and the relationship between FNE and OL2S. The study employed a survey method with 190 learners from a private high school participating in it. Based on the descriptive statistics, the learners generally had a moderate level of FNE and OL2S. The FNE analysis showed that they had self-perception of low English competence and were afraid to speak without preparation. In OL2S, the analysis suggested that the learners believed that people around them did not consider their English mastery a priority. Through correlation formula, the study found a positive yet weak correlation between learners’ FNE and their OL2S. It suggested that the higher learners’ FNE, the higher they perceived responsibility to avoid negative outcomes. Besides, the finding also suggested that English instruction could be designed in such a way to attract the interest of learners from non-English language streams to give their best and promote active collaboration to lessen self-comparison among them. The limitations and contributions of the study were also discussed to provide possible directions for future studies.